Kikuchi-Fujimoto Disease: A Diagnostic Challenge in Histiocytic Necrotizing Lymphadenitis – A Case Report (KYAMC Journal, 2026)
Kikuchi-Fujimoto disease (KFD) is a rare, self-limiting lymphadenitis characterized by fever and cervical lymphadenopathy. Its etiology is unclear but is linked to immune responses to viral or bacterial infections. Diagnosis relies on histopathological examination due to similarities with tuberculosis, lymphoma, and systemic lupus erythematosus (SLE). This case report highlights a 39-year-old woman initially misdiagnosed with tuberculosis, later confirmed to have KFD. Awareness and accurate differential diagnosis are crucial for appropriate management and avoiding unnecessary treatment.KYAMC Journal Vol. 16, No. 03, October 2025: 156-159.